The Risk of COVID-19 Related Hospitalsation, Intensive Care Unit Admission and Mortality in People With Underlying Asthma or COPD: A Systematic Review and Meta-Analysis - Pardhan, Shahina; Wood, Samantha; Vaughan, Megan; Trott, Mike (Frontiers in Medicine, 2021)
Background: Several underlying diseases have been associated with unfavourable COVID-19 related outcomes including asthma and Chronic Obstructive Pulmonary Disease (COPD), however few studies have reported risks that are adjusted for confounding variables. This study aimed to examine the adjusted risk of COVID-19 related hospitalisation, intensive care unit (ICU) admission, and mortality in patients with vs without asthma or COPD. Methods: A systematic review of major databases was undertaken for studies published between 1/12/2019 to 19/4/2021. Studies reporting the adjusted (for one or more confounder) risks of either hospitalisation, ICU admission, or mortality in asthmatics or COPD patients (control group=no asthma or no COPD) were identified. Risk of bias was determined via the QUIPS tool. A random effect meta-analysis was undertaken. Findings: 37 studies were eligible for analysis, with a total of 1,678,992 participants. The pooled ORs of COVID-19 hospitalisation in subjects with asthma and COPD was 0.91 (95%CI 0.76-1.09) and 1.37 (95%CI 1.29-1.46) respectively. For ICU admission, OR in subjects with asthma and COPD was 0.89 (95%CI 0.74-1.07) and 1.22 (95%CI 1.04-1.42) respectively. For mortality, ORs were 0.88 (95%CI 0.77-1.01) and 1.25 (95%CI 1.08-1.34) for asthma and COPD respectively. Further, the pooled risk of mortality as measured via Cox regression was 0.93 (95% CI 0.87-1.00) for asthma and 1.30 (95% CI 1.17-1.44) for COPD. All of these findings were of a moderate level of certainty. Interpretation: COPD was significantly associated with COVID-19 related hospital admission, ICU admission, and mortality. Asthma was not associated with negative COVID-19 related health outcomes. Individuals with COPD should take precautions to limit the risk of COVID-19 exposure to negate these potential outcomes. Limitations include differing population types and adjustment for differing cofounding variables. Practitioners should note these findings when dealing with patients with these comorbidities. Funding: There was no funding for this study. Registration: This review was registered with PROSPERO: CRD42020194155.